(untitled) (Research, Society and Development, 2023)
This article addresses the issue of medication poisoning in Brazil, with a special focus on the Southern region. The research revealed a high number of cases of medication poisoning, with women and individuals between 20 and 39 years old being the most affected. Suicide attempts were identified as the primary cause of medication poisoning. The study emphasizes the crucial role of pharmacists in the prevention and management of these poisonings, highlighting the importance of their expertise in medication knowledge. Ease of access to medications, self-medication, and lack of proper information regarding dosage and administration were identified as contributing factors to medication poisoning. Additionally, the research highlights the influence of advertising and the complexity of some medication formulations as factors contributing to the problem. The data shows that medication poisoning is a significant public health issue in Brazil, with a substantial social and economic impact. Adequate preventive strategies, the integration of pharmacists into multidisciplinary teams, and health education are crucial to reducing the rates of medication poisoning and promoting responsible medication use. The research also underscores the need for public policies targeting at-risk groups to prevent suicide and raise awareness about the dangers of self-medication. In summary, medication poisoning represents a significant challenge for public health in Brazil, and the role of pharmacists plays a fundamental role in mitigating this problem.